2000
DOI: 10.1099/0022-1317-81-4-1121
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (−)-strand RNA from the 3′ untranslated region of plant viral genomes expressed in transgenic plants upon infection with related viruses

Abstract: Potyviruses and cucumoviruses are agronomically important groups of (j)-stranded plant RNA viruses, but they are strikingly different both structurally and in their modes of expression and replication. The potyviruses (Potyviridae) are members of the Picorna-associated supergroup, and have a monopartite, polyadenylated RNA genome, which is covalently linked to a small peptide (VPg) at its 5h end. The viral RNA is encapsidated in flexuous rod-shaped particles, and encodes a single polyprotein which is co-and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The 3¢ UTR is highly conserved among all of these full genome sequences (usually more so than even the CP coding region) suggesting that potent purifying selection may preserve secondary structures and/or sequence motifs involved in RdRp complex formation [34,35]. Unlike the 3¢ UTR, the 5¢ UTR was the most divergent genome region.…”
Section: Recombination Analysismentioning
confidence: 99%
“…The 3¢ UTR is highly conserved among all of these full genome sequences (usually more so than even the CP coding region) suggesting that potent purifying selection may preserve secondary structures and/or sequence motifs involved in RdRp complex formation [34,35]. Unlike the 3¢ UTR, the 5¢ UTR was the most divergent genome region.…”
Section: Recombination Analysismentioning
confidence: 99%
“…It should be noted, however, that a cellular exclusion phenomenon limits the number of cells in which both subgroups are present (Takeshita et al ., ). By contrast, as the plants expressing the CP+3′UTR of R‐CMV (subgroup II) are fully susceptible to I17F‐CMV (subgroup I), the transgene mRNA and viral RNA will both be present in all infected cells (Jacquemond et al ., ). Template switching by the viral replicase between the transgene mRNA and the RNA of the non‐target viral genome occurs, creating messenger/viral RNA recombinants One of the first pieces of evidence that this could occur was the demonstration that, when transgene mRNA contains the CMV 3′UTR, the 3′UTR promoter can be recognized by the viral replicase to synthesize complementary RNA (Teycheney et al ., ). Several papers have demonstrated that recombination does indeed occur in transgenic plants expressing CMV CP genes on infection with a divergent strain of CMV (Turturo et al ., ; Morroni et al ., , ). The population of messenger/viral RNA recombinants includes variants not produced by the equivalent virus/virus recombination If recombination occurs in VRTPs, the recombinant viruses could lead to a novel disease only if they were different from those occurring in non‐transgenic plants.…”
Section: Evaluation Of Whether Recombination In Plants Expressing a Cmentioning
confidence: 97%
“…In a recent study, Turturo et al (2008) were the first to succeed, using transgenic plants expressing the coat protein (CP) and the 39-non-coding region (39-NCR) of RNA3 of a subgroup II strain of cucumber mosaic virus (R-CMV). The 39-NCR can serve as an initiation site for the viral replicase (Teycheney et al, 2000), thus making it possible for full-length recombinant RNA3 that can potentially be replicated to be produced by a single crossover. Turturo et al (2008) showed clearly that the populations of recombinant viral RNAs were similar in the transgenic plant system when infected with a subgroup I CMV (I17F-CMV) and in the non-transgenic plants infected simultaneously with both CMV strains.…”
Section: Introductionmentioning
confidence: 99%